2018
DOI: 10.1002/ddr.21503
|View full text |Cite
|
Sign up to set email alerts
|

Alignment‐based design and synthesis of new antimicrobial Aurein‐derived peptides with improved activity against Gram‐negative bacteria and evaluation of their toxicity on human cells

Abstract: Considering the worldwide increasing prevalence of resistance to traditional antibiotics, it is necessary to find new antibiotics to deal with this issue. Recently, antimicrobial peptides (AMPs) have been proposed as new antimicrobial agents. Aureins are a family of AMPs that are isolated from Green and Golden Bell Frogs. These peptides have a favorable antibacterial activity against Gram‐positive bacteria. We designed two peptides derived from natural Aurein enjoying alignment‐based design method. After synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…It has a strong ability of immune regulation and inhibition of TNF-α production from LPS (21). It was reported that when the concentration of AMP was 10-20 μg/mL, it had an excellent bactericidal effect and biological activity (22).…”
Section: Discussionmentioning
confidence: 99%
“…It has a strong ability of immune regulation and inhibition of TNF-α production from LPS (21). It was reported that when the concentration of AMP was 10-20 μg/mL, it had an excellent bactericidal effect and biological activity (22).…”
Section: Discussionmentioning
confidence: 99%
“…All of our final epitopes were in the suitable range in this regard. Increasing the hydrophobic ratio in the non-polar face of the peptides to increase the symmetry in hydrophobic and hydrophilic faces, can enhanced their toxicity and hemolytic activity (Boland and Separovic 2006;Madanchi et al 2019). Helical wheel projection showed that in all epitopes, the hydrophilic face became more discontinuous by polar residues, so the symmetry in hydrophobic and hydrophilic faces was not seen in our epitopes.…”
Section: Antigenmentioning
confidence: 89%
“…In general, peptides can be modified by the methods of lipidation, glycosylation, and cyclization to enhance their protease resistance and improve their antibacterial activities [ 25 ]. In this case, we designed and synthesized a series of stapled Aurein1.2 peptides that exhibited improved proteolytic stability and higher helical contents than their linear counterparts.…”
Section: Discussionmentioning
confidence: 99%